The Effect of Child Sexual Abuse on Social Functioning in Schizophrenia Spectrum Disorders - López-Mongay, Daniel (Journal of interpersonal violence, 2021)
The objective of this study was to explore social functioning in schizophrenic patients who have suffered child sexual abuse (CSA) in comparison with those who have not suffered from it in a Spanish sample of 50 patients with schizophrenia or schizoaffective disorder. The Quality of Life (QOL) Scale, the Childhood Trauma Questionnaire (CTQ-SF), and the NEO Five Factor Inventory (NEO-FFI) were administered in this study. We found a CSA prevalence of 22% in our sample. Results showed that QOL global scores reduced by 9.34% at a statistically significant level (p = .037) in sexually abused patients in comparison with those who did not report experiencing sexual abuse. Regression analysis in the QOL scales showed no differences in intrapsychic foundation scores or in the social relations scale. Scores in the instrumental role scale were reduced by 4.42 points in patients with CSA (p = .009). Neither neuroticism nor extraversion results differ between the trauma group and those who did not suffer trauma. Clinical implications of these results are discussed.